Workflows for spatial ex ante economic analysis of agronomy interventions : Version 0.1 - Mkondiwa, Maxwell; Chamberlin, Jordan; Oyakhilomen Oyinbo (EiA, 2024)
This manual provides workflows for conducting spatial ex ante economic analysis of agronomic interventions. The statistical, mathematical and economic concepts in these workflows are already available in different books and journal articles. We especially leveraged the classic text by Alston et al (1995) that summarized all the methods for evaluating agricultural research and development innovations. Our task was simply to organize the different methods that spawned after Alston et al (1995) as standard operating procedures (SOPs) —i.e., analytical procedures that can be reproducible and replicated in other contexts. We also focused on how to transition from country level analyses that characterized that era to spatially gridded applications that recognize the heterogeneity associated with smallholder farming systems. In this manual, you will learn how to conduct spatially explicit (mostly gridded) economic evaluation of agronomic innovations with R and other programming software including Octave, and python. Our purpose for these SOPs is to standardize the spatial ex ante economic analysis process with the aim of reducing the amount of time researchers spend on coding the common building blocks of spatial ex ante workflows and improving their efficiency. The choice of which methods to showcase in the SOP reflects our primary goal which is to provide a simple and easy-to-use prioritization assessment framework for potential agronomic investments, which can be applied by economists, non-economists, project managers, and students. We focus on three indicators for prioritization: yield gains, profit gains and robustness to risk. These have been recognized as some of the key indicators for assessing agronomic gains to technology.